THE ASYMPTOTIC DISTRIBUTION OF TRACES OF WEAK MAASS FORMS. Issue 4 (3rd August 2021) - Khaochim, Narissara; Masri, Riad; Tsai, Wei‐Lun
Abstract: We give an asymptotic formula with a power saving error term for traces of CM values of a generic class of weak Maass forms. We apply this result to study the asymptotic distribution of several arithmetic functions, including the partition function, the Andrews smallest parts function, and the coefficients of Ramanujan's mock theta function f ( q ) .